Supersonic gas curtain based ionization beam profile monitor for FLASH proton beam therapy - Patel, Milaan; Kumar, Narender; Thesni, Farhana; Butcher, William; Price, Tony; McLauchlan, Ruth; Welsch, Carsten P. (Frontiers in Oncology, 2025)
IntroductionFLASH Proton Beam Therapy (FLASH-PBT) combines the precision targeting ability of proton beam with radiobiological advantage of FLASH effect at ultra-high dose rates (> 40 Gy/s) to improve tumor control while reducing the damage to surrounding healthy tissues. The commonly used spot-scanning proton therapy technique relies on real-time beam monitoring to provide feedback to the accelerator for spot switching. This study introduces a novel Supersonic Gas Curtain Ionization Profile Monitor (SGC-IPM) for non-invasive, high-resolution proton beam profile monitoring, aiming to provide real-time feedback to medical accelerators.MethodsThe SGC-IPM uses a supersonic gas jet shaped into a curtain to measure the 2D transverse profile of the beam. Initial tests of the device was conducted on a DC Pelletron accelerator at Dalton Cumbrian Facility (DCF), Whitehaven, UK, followed by later tests on MC40 cyclotron at the University of Birmingham (UoB), UK. Across both the experiments, the device was directly coupled to the vacuum side of the beamlines and beam profiles were recorded for protons at energies ranging from 4–28 MeV and currents ranging from 1–100 nA, with various beam sizes and shapes.ResultsThe SGC-IPM successfully measured beam profiles and demonstrated a linear response to beam currents across the measurement range, and its response at different energies was quantified by introducing an energy-dependent detection factor, D which is used to quantify the sensitivity of the device. The detector was upgraded after the first set of experiments at DCF resulting in sensitivity improvement by a factor of 80 in later experiments at UoB.DiscussionsA mathematical model is introduced to show that device’s response depends on particle fluence, a quantity independent of dose rate. It’s linear response to beam current is used to extrapolate measurements at conventional dose rates to assess its performance at FLASH dose rates. The performance is evaluated in terms of threshold dose required to measure beam profile for a standard 1-liter clinical volume positioned 15–20 cm deep in water.ConclusionThis study presents a viable solution for non-invasive proton beam profile monitoring for FLASH-PBT. The device shows a linear response to beam current within the measurement range. The mathematical model quantifies the device’s sensitivity and provides a means to calibrate it for dose estimation.